A model with explicit expectations for Belgium - Philippe Jeanfils (National Bank of Belgium, 2000)
This paper presents a new quarterly macroeconometric model of the Belgian economy. It is intended to contribute to existing analytical work covering the specific transmission mechanisms of the euro area monetary policy in the Belgian economy. It also contributes to the forecast exercises and to their risk analysis. Finally it is also used to analyse the consequences of specific Belgian shocks. The model is small-scale and based on recent macroeconomic theory. The model's dynamics not only allow for the lagged adjustments from economic agents due to transaction costs to be taken into consideration, but also for agents to anticipate future developments and policy reactions. In simulations, expectation formation can be assumed either to be model consistent or to be generated by VAR-based extrapolations. On the basis of a few diagnostic simulations it is shown that in the long run the model converges to its steady state, defined by the underlying economic theory.
Keywords: 330; Makroökonometrie; Schock; Steuerpolitik; Arbeitsangebot; Belgien